Hypersensitivity in ALK-positive lung cancers exposed to ALK inhibitors: a case of successful switch to an alternative ALK inhibitor and systematic review of the literature - Deng, Lei (Lung Cancer (Auckl), 2018)
Alectinib can cause rare, but severe hypersensitivity. The cross-reactivity between different ALK inhibitors is unknown and desensitization is the only reported management. We hereby report the first case of severe delayed hypersensitivity developed in a lung cancer patient treated by alectinib, who was successfully managed by switching to brigatinib, another ALK inhibitor. The patient achieved excellent anti-tumor response to brigatinib. Our case provides an alternative and safe strategy in patients with alectinib-related hypersensitivity.